Anxiety and alcohol in the working‐age population are driving a rise in mental health‐related emergency department presentations: 15 year trends in emergency department presentations in Western Australia. (1st July 2019) - Yap, Matthew; Tuson, Matthew; Whyatt, David; Vickery, Alistair
Abstract: Objective: To evaluate age, gender and disease‐specific trends in ED for mental health presentations over 15 years. Methods: The study population consisted of residents of metropolitan Perth, Western Australia, presenting to Perth ED between 1 July 2002 and 30 June 2017. Population rates of mental health‐related ED presentations per year were calculated. Results: Rates of mental health ED presentations are significantly increasing in the working‐age population for those with stress and anxiety‐related diagnoses, particularly in younger females, and also for alcohol‐related presentations for those aged 10–49 years, particularly in males. Conclusion: The present study demonstrates that increased rates of mental health‐related ED presentations are driven by increased rates of presentation for stress and anxiety‐related and alcohol‐related presentations in both genders across the working‐age population.